NETWORKING AS A COMPONENT OF FORMING SOCIAL CAPITAL: THE ECONOMIC ASPECT - Halushka, Zoia; Nafus Inna (International Journal of Innovative Technologies in Social Science, 2020)
The article analyzes the nature and economic importance of social networks as one of the components of social capital. It is shown that the economic component of social capital is associated with the ability to obtain certain economic benefits from its use. Mechanisms for the accumulation of social capital contain the involvement in these processes of all its components - trust, norms, values, social networks. The network approach of J. Coleman to substantiation of economic essence of social capital is analyzed. The necessity, possibility and directions of influence of social networks on formation and increase of efficiency of social capital have been proved. The types of social networks and the possibilities of their influence on creation of connecting, horizontally-integrating and vertically integrating social capital are revealed. The rating of social networks and examples of their use to increase the efficiency of functioning of social capital are given. It is proved that networks are formed not chaotically, but purposefully, given the subjective vision of the feasibility of such interaction, and their use can have both positive and negative consequences. The possibility of using social networks to form a service-oriented state is indicated.